2013
DOI: 10.1583/12-4063.1
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Mechanical Performances of 8 Marketed Aortic Stent-Grafts

Abstract: Stent design strongly influences mechanical performances of aortic stent-grafts. Spiral and circular stents provide greater flexibility, as well as lower stress values than Z-stents, and thus better durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 33 publications
5
89
0
Order By: Relevance
“…At the moment, simulation results could be post-processed to estimate luminal areas along the vessel centreline (De Bock et al, 2012;Demanget et al, 2013) and stents apposition defects (De Bock et al, 2014;Perrin et al, 2015b). These estimates could point out possible SG kink, gap between SG and arterial wall or collateral artery coverage, and thus potential risk of thrombosis, endoleak or artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, simulation results could be post-processed to estimate luminal areas along the vessel centreline (De Bock et al, 2012;Demanget et al, 2013) and stents apposition defects (De Bock et al, 2014;Perrin et al, 2015b). These estimates could point out possible SG kink, gap between SG and arterial wall or collateral artery coverage, and thus potential risk of thrombosis, endoleak or artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Gandini et al 12 reported a case of successful use of the Ovation stent graft in a challenging case of aortoiliac anatomy combining a narrow (14 mm) calcified bifurcation with a calcified, narrow iliac 21 The combination of these features enhances the flexibility of the iliac limbs and may attribute to the optimal clinical performance of Ovation to confront challenging iliac anatomies, providing better stent interlocking during bending and, thus, lower luminal reduction. 22,23 Therefore, although the IFU of the particular endograft suggest an inner iliac wall diameter of 8 mm, the reported results in the literature advocate the use in much smaller diameters. The lack of nitinol support from the main body and iliac limb gates may render the contralateral iliac limb of the endograft prone to compromisation or collapse against the AAA sac wall in cases of a tight endoluminal space due to narrow aortoiliac bifurcation and eccentric intraluminal thrombus, complicating its catheterization and increasing the intraprocedural difficulties.…”
Section: Discussionmentioning
confidence: 94%
“…More intriguingly, as modeling techniques evolve, finite element analysis can be performed for direct comparisons of the mechanical stresses and strains acting on a number of commerciallyavailable device components under a variety of angulations, depicting potential advantages or drawbacks between them. 23 …”
Section: Biomechanical Approach Of Aortic Stent-grafts: What Is To Bementioning
confidence: 99%